PRACTICAL SIGNIFICANCE OF LEZGIN PROVERBS, SAYINGS AND RIDDLES (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-2-108-116The article analyzes the practical significance and pragmatic functions of aphoristic genres (proverbs, sayings, riddles) of Lezgin folklore. To understand the feasibility and usefulness of verbal formulas, the principle of evaluation is applied – pragmatism. As a result, the author carefully examines the artistic component of the genres presented. A distinctive feature of these genres is structural and semantic differences. It has been proven that folk paremias and riddles consist of a descriptive component – the “object/object” construction and commenting. It is noted that the meaning of definitely affirmative and alternative judgments in the value system, expressed in Lezgin folk proverbs and sayings, cannot be understood without taking into account the practical component of publicly available thought. The main function of the Lezgin paremias is communicative. The question is raised about how folk riddles operate in relation to the basic pragmatic aspects of normal communication. It has been established that the principles of pragmatics are fundamentally non-standard, that is, they are motivated in terms of conversational goals. The main goal of solving riddles is to lead all participants in the interaction to understand and agree on the special logic of individual riddles. On the basis of a pragmatic analysis of the aphoristic genres of Lezgin folklore, it is proven that riddles do not exist as questions, but act as entimemes in the same way as proverbs.Key words: Lezgin folklore, aphoristic genre, proverbs, sayings, riddles, practical significance, pragmatism, entimemes